2014
DOI: 10.4209/aaqr.2013.04.0121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Assessment (LCA) of Accelerated Carbonation Processes Using Steelmaking Slag for CO2 Fixation

Abstract: Carbon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Giannoulakis et al 29 performed a LCA study for a power plant and showed that the implementation of CCS by mineralization could reduce life cycle GHG emissions by 15-64% but would increase the levelized cost of electricity by 90-370% compared to a reference power plant without CCS. Xiao et al 30 studied the mineralization of steel slag via several pathways and showed that key factors effecting the overall process are the particle size of alkaline solid waste, the rotating speed of the rotary packed bed, the solid/liquid ratio, and the reaction temperature. In another LCA study, Julcour et al 31 investigated the effect of mechanical exfoliation on mineralization to reduce emissions from a power plant.…”
Section: Introductionmentioning
confidence: 99%
“…Giannoulakis et al 29 performed a LCA study for a power plant and showed that the implementation of CCS by mineralization could reduce life cycle GHG emissions by 15-64% but would increase the levelized cost of electricity by 90-370% compared to a reference power plant without CCS. Xiao et al 30 studied the mineralization of steel slag via several pathways and showed that key factors effecting the overall process are the particle size of alkaline solid waste, the rotating speed of the rotary packed bed, the solid/liquid ratio, and the reaction temperature. In another LCA study, Julcour et al 31 investigated the effect of mechanical exfoliation on mineralization to reduce emissions from a power plant.…”
Section: Introductionmentioning
confidence: 99%
“…Several capture technologies exist and various applications have been studied over the past 2 decades (Cuéllar-Franca and Azapagic 2015). Among the existing techniques, mineral carbonation allows the capture of CO 2 inside rocks, such as serpentinite, or waste such as steel making slags and platinum tailings (Khool et al, 2011;Nduagu et al, 2012;Giannoulakis et al, 2014;Xiao et al, 2014;Ostovari et al, 2020). CCU is particularly interesting for industrial solid waste, allowing a double advantage by capturing carbon dioxide and offering waste valorization, despite high energy issues (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since the environmental awareness of the public has increased, the odors caused by treatment plants have become a new and troublesome social problem. Another study suggests that municipal waste management in China tends to incinerate instead of landfill, but it causes social conflicts as it impedes the construction of treatment plants near public land or habitats [28].…”
Section: Life Cycle Assessment Of Sewage Managementmentioning
confidence: 99%